OP0287 Calcium Pyrophosphate Dihydrate Crystals Induce IL-1β Production by Monocytes through A Potassium Efflux-Dependent Pathway. (15th July 2016) - Campillo-Gimenez, L.; Renaudin, F.; Bobé, P.; Gosset, M.; Combes, C.; Cohen-Solal, M.; Lioté, F.; Ea, H.-K.
Abstract : Background: Osteoarthritis (OA) is the most common adult rheumatic disease characterized by cartilage degradation, synovial inflammation and subchondral bone remodeling. Risk factors associated with OA are age, genetics, mechanical overload and presence of calcium-containing microcrystals. Calcium pyrophosphate crystals including monoclinic and triclinic dihydrate phases (m- and t-CPPD) are found in 40% of end-stage OA patients. Frequently asymptomatic, it can give rise to synovitis contributing to OA lesion worsening. CPP crystal-induced inflammation is orchestrated mainly by interleukin (IL)-1β. Secretion of IL-1β required a cytokine maturation process which depends on the NLRP3 inflammasome activation. This intracellular multiprotein complex can be stimulated by ATP-dependent potassium (K + ) efflux, reactive oxygen species (ROS) generation, lysosomal or mitochondrial alterations. Objectives: The objectives were to identify intracellular pathways induced by CPPD crystals and leading to NLRP3 activation and IL-1β production. Methods: The effects of CPPD crystals were assessed in human THP-1 cell line and bone marrow-derived macrophages (BMDM) from wild type (wt), NLRP3 ( nlrp3 –/– ) or P2X7 receptor ( p2x7 –/– ) knock out mice. Cells were primed before stimulation with synthetic m- and t-CPPD crystals in presence or absence of K + -enriched media (KCl 50mM – to block K + efflux), N-acetyl-L-cystein (NAC 50mM – an intracellular ROS scavenger) or oxidized ATP (oxATP 200μM – an antagonist of ATP). NLRP3 expression was determined by western blotting, IL-1β and extracellular ATP (ATPe) concentrations were measured in cell culture supernatants whereas ROS production and mitochondrial membrane potential were evaluated using fluorescent probes (DFDA and JC-1, respectively). Results: First, IL-1β production induced by CPPD crystals was lacking in nlrp3 –/– BMDM but important in wt BMDM. Second, we showed that m-CPPD crystals induced a higher NLRP3 expression and IL-1β production than t-CPPD suggesting a differential modulation of NLRP3 activation. We observed that CPPD-induced IL-1β secretion was completely abrogated when K + efflux or intracellular ROS were inhibited. Moreover, we demonstrated a stronger decrease in mitochondrial membrane potential following m-CPPD than t-CPPD crystal stimulation, combined with a de novo ROS generation. These two latter effects were inhibited when K + efflux was blocked. Finally, we found that m- and t-CPPD crystals differentially brought on an ATP release and that IL-1β production was partially inhibited by oxATP. However, although ATPe can trigger K + efflux through P2X7 receptor opening, crystal-mediated IL-1β production was similar between wt and p2x7r –/– BMDM. Conclusions: IL-1β production triggered by m- and t-CPPD crystals occurred through a modulation of ROS production and mitochondrial disruption. Interestingly, K + efflux, associated with ATP release, could be the initial signal of CPPD-induced IL-1β maturation, independently of P2X7 receptor involvement. These results highlight a new molecular pathway of crystal-dependent OA inflammation. Disclosure of Interest: None declared